Impact of Extraneous Cognitive Load on Multimedia based Grammar Learning: A Comparative Study - Nadia, Refat; Hafizoah, Kassim (American Scientific Publisher, 2018)
Cognitive load is a theoretical notion having an increasingly influential role in the educational research areas that asserts that cognitive capacity in working memory is limited where too much load on the cognitive system may hamper the total learning process and learning outcome. Intrinsic cognitive load, extrinsic load and germane cognitive load are three types of cognitive load. There is a strong link between extraneous cognitive load and instruction design which recognizes that learning materials can overload a learner’s cognitive effort. It has a negative influence on learning performance which has not been focused yet for multimedia based grammar learning. The present work thus sets out to explore how much difference occurs on human cognition with two different types of multimedia based instructions. To conduct the research, a quantitative research method was adopted with the use of two instruments (online test and NASA- TLX) to measure the impact (performance outcome and extraneous cognitive load) of the two type instructions on learners. The instruments are used with a view to 1) identify performance variation of the students on different tasks through online test 2) measure mental workload with NASA task load index. The findings revealed that the instructions with proper maintain principles of cognitive theory of multimedia learning have better performance and low cognitive overload on students than that of the instructions with violating the cognitive principles of multimedia learning.